THE FACTORS OF JOB STRESS AND COPING STRATEGIES AMONG SECONDARY SCHOOL TEACHERS DURING COVID-19 PANDEMIC - Stephenie Stefert, Peter (Universiti Malaysia Sarawak (UNIMAS), 2021)
The aim of this study was to investigate the factors of job stress and coping strategies among secondary school teachers during Covid-19 pandemic and their strategies to cope with the stressors. This study is an explorative study. This research is conducted qualitatively to get an in-depth understanding of the knowledge of job stress and coping strategies. The sampling method used in this study is convenience sampling, where informants are chosen based on their suitability of sources of the data in which the research area are concern. There are 6 informants that has been chosen to participate in this study. Data for this study were collected through a semi-structured interview and open-ended questions and were analyse by using content analysis approach. The finding of this study has showed that the factors that contribute to job stress among secondary school teachers can be divided into two categories which is environmental stressors and individual stressor. Environmental stressors were such as work-overload and technological changes, while individual factor were such as role ambiguity. The finding also has highlight two coping strategies that were commonly used by teachers to cope with the identified stressors, which is problem-focused coping strategies and emotion-focused coping strategies. Problem-focused strategies were such as leisure and meditation while emotion-focused strategies were such as create flexible timetable.This study also has highlighted some implication for the institution, HR practitioners and also some recommendation for future research.